Investigating the relationship between serum magnesium levels and the degree of tumor in breast cancer patients (Latakia University Journal -Medical Sciences Series, 2024)
Background: Breast cancer is a deadly disease caused by the accumulation of mutations that lead to the uncontrolled growth of cells in breast tissue ,the relationship between magnesium and cancer formation is intricate ,some researches have shown that an imbalance in magnesium levels is often found in tumor cells ,and both magnesium deficiency and supplementation can impact the development of tumors.Numerous studies have explored the effect of magnesium deficiency on tumor incidence and the progression of existing tumors.Aim: To determine serum levels of magnesium in newly diagnosed female breast cancer patients and to assess their association with some prognostic factors in breast cancer pateints.Design and methods: This study is done on 79 newly diagnosed female breast cancer patients and 29 age matched apparently healthy female volunteers as controls. Serum samples from all patients and controls were subjected to magnesium measurementResults: In the breast cancer group, the median serum levels of magnesium were1.99 mg/dl , while it was 2.48 mg/dl in the control group. Deficient Mg levels were detected in 26/79 (33%) of the breast cancer patients and 0/29 (0%) of the control group. the tumor characteristics of the breast cancer patients (histology, grade, stage, and receptor status) did not show any significant associations with serum levels of magnesiumConclusion: deficient levels of magnesium might contribute to the development of cancer. Further studies with larger number of patient are needed.